Гендерні особливості ресурсності поліцейських - Шевченко, Л. О.; Shevchenko, L. O.; ORCID: http://orcid.org/0000-0002-6117-9134; Лещенко, О. С.; Leschenko, O. S.; ORCID: http://orcid.org/0000-0003-3069-7235 (Право і безпека. – 2017. – № 4 (67). – С.216-221, 2017)
Актуальність теми пов’язана з потребою вивчення ресурсності працівників поліції обох статей. Представлено результати емпіричного вивчення гендерних особливостей психологічної ресурсності працівників поліції, серед яких виявлено такі: у групі жінок сформованими психологічними ресурсами є «робота над собою» та «любов», у групі чоловіків – «успіх». Установлено взаємозв’язки між компонентами психологічної ресурсності та факторами прийняття рішень у групах досліджуваних: чоловіки схильні до продуктивного копінгу «пильність», жінки частіше орієнтуються на копінг «уникнення».

The urgency of the chosen topic, which is related to the need to study the potential of police officers of both sexes, has been outlined. The latest research on the chosen issues of Ukrainian and foreign scholars has been analyzed, and the objective of the article was to present the results of an empirical study of gender characteristics of psychological potential of police officers. According to the results of the study, the authors have revealed a lack of gender differences in the level of psychological potential within studied persons: 68% of future patrol police officers have a high level of potential; 27% has the studied persons with the average level of psychological potential of sample group; and the smallest – about 5% – is the group with low level of psychological potential. The gender features of potential have been revealed: formed with psychological resources in the group of women are “work on themselves” and “love”, in the group of men – “success”. The most developed psychological resources in both groups of the studied persons were “self-realization in the profession”, “self-confidence”, “help to others” and “responsibility”, which can be considered as a factor of changes in both professional development and personal self-development. The relationships between the components of psychological potential and decision-making factors in the groups of studied persons have been established: the ability of women to update their own resources and the desire to creatively work on them increases their tendency to rationality, moderation and procrastination, and the presence of such gender-colored features as sensitivity, empathy and openness to people, predetermine the probability of implementing such decision-making factor as “avoidance”. Actualization of the ability to use own resources of men and the desire for self-realization strengthens their ability to take responsibility and diligence, allows to choose the most appropriate options for behavior and rational decisions, decreasing conformism; in a situation of decision-making they are prone to productive coping “vigilance”. The obtained data allow to study sources of potential of police officers (both men and women), to determine the ways to optimize their psychological potential and provide an opportunity to more effectively organize the psychological support of their professional activities.

Актуальность темы связана с необходимостью изучения ресурсности полицейских обоих полов. Представлены результаты эмпирического изучения гендерных особенностей психологической ресурсности работников полиции, среди которых выявлены такие: в группе женщин сформированными психологическими ресурсами являются «работа над собой» и «любовь», в группе мужчин – «успех». Установлены взаимосвязи между компонентами психологической ресурсности и факторами принятия решений в группах испытуемых: мужчины склонны к продуктивному копингу «бдительность», женщины чаще ориентуються на копинг «избегание».
Gender peculiarities of police officers’ potential
Гендернные особенности ресурсности полицейских
Шевченко, Л. О. Гендерні особливості ресурсності поліцейських / Л. О. Шевченко, О. С. Лещенко // Право і безпека. – 2017. – № 4 (67). – С.216-221.
Shevchenko, L.O. and Leshchenko, O.S. (2017), “Gender peculiarities of police officers’ potential” [“Henderni osoblyvosti resursnosti politseiskykh”], Pravo i Bezpeka, No. 4, pp. 216–221.
Keywords: Психологія. Рsychology. Психология; Юридична психологія. Legal psychology. Юридическая психология; Наукові публікації. Scientific publications. Научные публикации; психологічна ресурсність; самореалізація; індивідуальний стиль прийняття рішень; копінг; чоловік; жінка; патрульна поліція; поліція; полиция; psychological potential; self-realization; individual decision-making style; coping; man; woman; patrol police; police; психологическая ресурсность; самореализация; индивидуальный стиль принятия решений; копинг; мужчина; женщина; патрульная полиция